2004
DOI: 10.1121/1.1738454
|View full text |Cite
|
Sign up to set email alerts
|

The corono-apically varying ultrasonic velocity in human hard dental tissues

Abstract: The speed of ultrasound at 20 MHz is measured for hard dental tissues inside human teeth. This includes the cementum, for which no data are available. The spatial distribution, extrema, and means of the longitudinal ultrasound velocity (LUV) are determined with an emphasis on the apical thirds and an extended spectrum. Tissue areas are investigated by optical means and by acoustical scanning, in order to compare apical regions-of-interest with the complete mineralized wet porous tissue that lies beneath the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…This is consistent with prior studies, and is likely due to the variation in density and elastic modulus both within and among the samples. 1,8,11 A t-test revealed that there was a negligible statistical difference between longitudinal and crosssectional samples of enamel ͑P = 0.44͒; however, the difference between longitudinal and crosssectional samples of dentin was significant ͑P = 0.003͒. Others have reported dependence of velocity on occluso-apical depth in longitudinal specimens of dentin.…”
Section: Resultsmentioning
confidence: 96%
“…This is consistent with prior studies, and is likely due to the variation in density and elastic modulus both within and among the samples. 1,8,11 A t-test revealed that there was a negligible statistical difference between longitudinal and crosssectional samples of enamel ͑P = 0.44͒; however, the difference between longitudinal and crosssectional samples of dentin was significant ͑P = 0.003͒. Others have reported dependence of velocity on occluso-apical depth in longitudinal specimens of dentin.…”
Section: Resultsmentioning
confidence: 96%
“…Table 3 Lateral variation in longitudinal ultrasound velocity of human dentin at a vertical level of 8 mm (LUV 8 ) relative to the crown reference X ¼ ðjx=w À 0:5jÞ Approximation at level y 0 ¼ 8 mm; (a ¼ a 8 Their absolute mean of the ultrasonic velocity was found in this study, too, especially for L_8-locations with relative width coordinates ranging between 0.25 and 0.5. The work with an initial ultrasonic velocity reported by Kossoff and Sharpe is frequently cited (Barber et al, 1969;Goss et al, 1978Goss et al, , 1980John, 2004John, , 2005Lees et al, 1973;Lo¨st et al, 1992;Mezawa et al, 1999;Ng et al, 1989;Wells, 1977). The corresponding value is represented here by the maximal LUVs that were observed at the L_8-level.…”
Section: Longitudinal Velocitymentioning
confidence: 89%
“…Since the velocities of the transverse waves (shear waves) do not depend on Poisson's ratios, and because propagating Rayleigh waves are less sensitive to changes in Poisson's ratio than longitudinal waves, it is furthermore quite desirable to initially gather information about the velocity of longitudinal waves in hard dental tissues. Experiments have already been performed that render a dynamic evaluation of hard dental tissues by utilizing longitudinal waves (Culjat et al, 2003;John, 2004;Lees et al, 1973;Louwerse et al, 2004).…”
Section: Ultrasonic Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The tooth model is composed of two concentric ellipses. The outer shell has material properties of enamel, the inner one those of dentin: Young's modulus vs. structure module 52.3 GPa and 31.14 GPa, Poisson's ratio 0.22 and 0.213, density 2950 kg/m 3 and 2200 kg/m³, damping factor 6.67 dB/MHz/cm and 10 dB/MHz/cm [1,3]. Due to lack of literature values the Poisson's ratio of enamel was estimated.…”
Section: Methodsmentioning
confidence: 99%